Adipose-Derived Mesenchymal Stem Cell Protects Kidneys against Ischemia-Reperfusion Injury through Suppressing Oxidative Stress and Inflammatory Reaction - Chen, Yen-Ta (BioMed Central, 2011)
BACKGROUND: Reactive oxygen species are important mediators exerting toxic effects on various organs during ischemia-reperfusion (IR) injury. We hypothesized that adipose-derived mesenchymal stem cells (ADMSCs) protect the kidney against oxidative stress and inflammatory stimuli in rat during renal IR injury. METHODS: Adult male Sprague-Dawley (SD) rats (n = 24) were equally randomized into group 1 (sham control), group 2 (IR plus culture medium only), and group 3 (IR plus immediate intra-renal administration of 1.0 × 10(6 )autologous ADMSCs, followed by intravenous ADMSCs at 6 h and 24 h after IR). The duration of ischemia was 1 h, followed by 72 hours of reperfusion before the animals were sacrificed. RESULTS: Serum creatinine and blood urea nitrogen levels and the degree of histological abnormalities were markedly lower in group 3 than in group 2 (all p < 0.03). The mRNA expressions of inflammatory, oxidative stress, and apoptotic biomarkers were lower, whereas the anti-inflammatory, anti-oxidative, and anti-apoptotic biomarkers were higher in group 3 than in group 2 (all p < 0.03). Immunofluorescent staining showed a higher number of CD31+, von Willebrand Factor+, and heme oxygenase (HO)-1+ cells in group 3 than in group 2 (all p < 0.05). Western blot showed notably higher NAD(P)H quinone oxidoreductase 1 and HO-1 activities, two indicators of anti-oxidative capacity, in group 3 than those in group 2 (all p < 0.04). Immunohistochemical staining showed higher glutathione peroxidase and glutathione reductase activities in group 3 than in group 2 (all p < 0.02) CONCLUSION: ADMSC therapy minimized kidney damage after IR injury through suppressing oxidative stress and inflammatory response.